Analisis Tingkat Toleransi dan Menghargai Perbedaan Dalam Konteks Pendidikan Kewarganegaraan di SMPN 35 Medan - Johan Pardamean Simanjuntak; Mima Defliyanti Saragih; Manotar Leryaldo Sinaga; Joy Novi Yanti Lumbantobing; San Mikael Sinambela; Ramsul Nababan (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
Citizenship education has a very important role in developing the attitudes and behavior of citizens who are tolerant, respect differences, and are able to communicate well with people from different backgrounds. Tolerance is a necessity to practice Pancasila values ​​as much as possible and ensure good relations between Indonesian people. Tolerance between religious communities means having the freedom to worship according to their respective religions and beliefs. There are no mutual prohibitions on practicing the worship they adhere to. This research uses descriptive qualitative methods by collecting data by conducting direct interviews. This research shows the importance of maintaining harmony, providing ethics in the opinions of other groups, upholding humanitarian principles and so on, which are expected to be able to bring glory to the country.